The Effect of Bridging Exercise and Heel Rises Exercise on Balance Post Stroke in Makassar City - Nurhikmawaty Hasbiah; Andi Rahmaniar Suciani P; Nurul Hidayah Akhmad; Aco Tang (UNIVERSITAS NEGERI MAKASSAR, 2023)
Post-stroke sensory motor disorders will also result in disturbances in the sensory and motor components which cause disturbances in the posture control system so that it is unable to maintain body balance in certain positions. One of the rehabilitation programs that are often used to restore function due to motor deficits is Bridging Exercise and Heel Raises Exercise. Bridging exercise is an exercise to strengthen and stabilize the gluteus, hip and lower back. This exercise is a great way to isolate and strengthen the gluteus and hamstring (back of the upper leg) muscles. Heel raises exercise is an exercise to strengthen the leg muscles, especially the gastrocnemius muscles and plantar flexion muscles which can have effects on the nerves and skeleton. From this stimulation, when it reaches proprioception, the body will maintain balance. The method used is a quasy experiment with a pretest-posttest two-group design. And it was found that the results of this study showed that there was an effect of bridging exercise 0.001 (p<0.05) and heel raises exercise 0.002 (p<0.05) in improving the balance of post-stroke patients. So it can be concluded that the two exercises can improve the balance of post-stroke patients.